Personal branding Strategies of English Language Educational Content Creators on Instagram: A Qualitative Study of Roy Muhammad - Arya Bima Prayoga; Muhammad Najih Farihanto (Universitas Negeri Yogyakarta, 2026)
The rapid development of social media has positioned personal branding as a crucial communication strategy, particularly for educational content creators in digital spaces. Instagram, with its visual and interactive features, serves as a strategic platform for building image, credibility, and audience engagement. This study examines the personal branding strategies employed by Roy Muhammad, an English language educational content creator on Instagram. Adopting a qualitative case study approach, data were collected through non-participant observation of Instagram content, semi-structured in-depth interviews, and documentation, and analyzed using thematic analysis. The findings reveal that Roy Muhammad’s personal branding is constructed through the integration of three key elements: performative differentiation, communication consistency, and audience-centered relevance. Differentiation is expressed through an engaging, humorous, and emotionally expressive communication style that captures audience attention; consistency is reflected in coherent narratives, educational values, and interaction patterns that foster trust; and relevance is achieved by addressing the real needs and challenges of the audience. This study contributes to digital communication scholarship by framing personal branding as a performative, relational, and contextually grounded strategic process within the social media ecosystem..